Розвідки в басейні р. Прут - Ільків, М.В.; Пивоваров, С.В. (Археологічні дослідження в Україні, 2010)
Results of archaeological prospecting in 2009 to the west from Chernivtsi along the lower flows of the Rivers Shubranets and Revnyak (Prut basin) are presented.